CENTENARY OF THE SCOTTISH INSTITUTE OF CHARTERED ACCOUNTANTS. - Murphy, Mary E. (The Accounting Review, 1955)
Abstract The article focuses on the centenary of the Scottish Institute of Chartered Accountants. The one hundredth birthday of the oldest accounting body in the world, The Institute of Chartered Accountants of Scotland was celebrated by two thousand people, including representatives of fifty-four professional societies, in Edinburgh in June 1955. In the welcome address by the president of the institute, the president stressed that the facts that a grant of a charter to a body was no warrant of monopoly and that the future of a great profession was not created by letters after a name, but by industry, integrity and service. That Institute members could say without fear of contradiction that their founders had created an honorable profession and a designation, 'chartered accountant,' known and respected all over the world. The Scottish Institute had a great tradition of service to the community, not only in Scotland but in every part of the world and it is with a full consciousness of our responsibilities that chartered accountants dedicate themselves to those higher aims.